Lexikographische Konzeption und kulturgeschichtliche Erkenntnis im digitalen Zeitalter - Lobenstein-Reichmann, Anja; Reichmann, Oskar (Lexicographica, 2020)
Digitization of dictionaries, which were founded in predigital times, face the challenge of modern technics. In the case of the Early New High German dictionary this challenge has proved to be more a chance than a curse. This article demonstrates how the textual structure of the (old) dictionary is transformed in the (new) digital language. It has shown that the new technics produce an added value. This is of course only possible under the condition, that the conception of the dictionary and the formulation by the lexicographer has prepared an elaborated base of semantic informations.
Gesehen am 08.02.2021